Trem2 exacerbates ischemic brain injury through Gpnmb in a photothrombotic stroke model - Xuezhen Chen; Kunyu Li; Siyu Liu; Junyi Zhao; Sagun Tiwari; Fan Zeng; Yue Zhao; Pingping Zhang; Han Tang; Hong Zhao; Helmut Kettenmann; Xianyuan Xiang; et al. (Proceedings of the National Academy of Sciences, 2026)
Ischemic stroke is a major public health challenge, with microglia-mediated neuroinflammation exerting both protective and detrimental effects on neuronal survival. The Triggering receptor expressed on myeloid cells 2 (Trem2), predominantly expressed by microglia, has been reported to confer neuroprotection in the middle cerebral artery occlusion (MCAO) model. Paradoxically, in patients, elevated plasma soluble Trem2 (sTrem2) levels correlate with increased risk and poor outcomes. To test the impact of Trem2 function in the context of stroke, we utilized the photothrombotic stroke model which elicited strong Trem2 upregulation, a clinical feature which is not mimicked in MCAO models. Trem2 depletion reduced infarction volume, suppressed proinflammatory cytokine production, preserved neuronal survival, and lessened motor and neurological impairment. Conversely, intracerebral administration of sTrem2 exacerbated neuronal loss, amplified inflammation, and worsened neurological deficits. Integrated mouse-human transcriptomic analyses identified glycoprotein nonmetastatic B (Gpnmb) as a conserved downstream effector of Trem2. Soluble Gpnmb (sGpnmb) administration abolished the protective effects of Trem2 depletion, promoting microglial activation, lipid accumulation, and neuronal damage. Additionally, plasma sTrem2 and sGpnmb levels were elevated in stroke patients, positively correlated, and may serve as biomarkers of poor prognosis. These findings uncover a detrimental role for Trem2 in ischemic stroke, provide mechanistic insight into the link between sTrem2 and poor clinical outcomes, and identify the Trem2–Gpnmb axis as a potential therapeutic target to mitigate poststroke neuroinflammation.